Creative STEM Pathways - Supporting Pacific Learners through 3D Printing - Margaret Flavell; Cherie Chu-Fuluifaga (New Zealand Journal of Teachers' Work)
The low participation of Pacific students in tertiary STEM studies has implications for schools as they consider how best to engage these learners in STEM subjects (Science, Technology, Engineering and Mathematics). This article reports on an innovative project that supports Pacific learners with STEM learning through 3D printing technology. Creative STEM Pathways is a university-led initiative which has successfully brought 3D technology to the classroom, providing culturally-sustaining, hands-on and relevant learning opportunities. We used an Appreciative Inquiry lens to help us explore how the programme could create positive learning experiences. In this article, we share experiences of its development and delivery. We highlight successes and challenges, offering practical insight to those considering similar innovation in the classroom.